Makna Pasemon dalam Syair-syair Musik Gereja: Kajian Semiotik Menurut Teori Charles Sanders Peirce - Alfa Kristanto; Michael Hari Sasongko; Dody Candra Harwanto (Institut Agama Kristen Negeri Manado, 2024)
Along with the dynamics of development, church music has also experienced extraordinary development. Meeting with many musical genres that are developing in society makes this music continue to be dialectic in such a way that it gives rise to new types of music that are used in Christian worship. In the development of the genre, it is increasingly difficult to distinguish between church music (liturgical music) and secular music, even though essentially, church music is different from secular music. Based on Charles Sanders Pierce's semiotic theory, the writing below attempts to analyze the pasemon in church music lyrics. Although church music and secular music have the same material object, both have different formal objects. This difference in objects is what makes its representation and interpretation different in its pair. This pasemon ultimately makes church music inseparable from the understanding of Christian theology. This is because essentially, in the context of Christian worship, church music is a means and not an end